Hadith Transmission: The Prophet's Approaches in Eschatological Narratives Related to Al-Fitan and Signs of The Hour - Khairun Nabilah Khairuddin; Mohd Yusuf Ismail (Universiti Sains Islam Malaysia, 2024)
Journal of Hadith Studies Volume 9 Issue 1 Page (156-167)